111 Improved Clinical Outcomes with Multi-Vessel Compared to Culprit only Percutaneous Coronary Intervention in Patients Presenting with Acute ST Elevation Myocardial Infarction. (6th June 2015) - Wilson, Simon; Chapman, Andrew; Whitaker, Eleanor; Cruden, Nicholas
Abstract : Introduction: In patients with acute ST elevation myocardial infarction (STEMI), percutaneous coronary intervention (PCI) improves survival. Multi-vessel coronary disease is identified in up to two thirds of patients and is associated with poorer outcomes. Historically, registry data and guidelines favoured culprit only PCI in STEMI, although recent data suggest that more complete revascularisation may improve outcomes. To examine this issue locally, we studied clinical outcomes in consecutive patients presenting with STEMI and multivessel disease in SE Scotland stratified according to revascularisation strategy (culprit versus multivessel angioplasty). Methods: We retrospectively examined clinical outcomes according to revascularisation strategy (culprit versus multi-vessel) in all patients with multivessel disease (defined as >70% lumen stenosis in at least one non-infarct artery that was suitable for revascularisation) undergoing PCI for STEMI in SE Scotland, October 2013 – August 2014. Patients with significant left main stenosis, cardiogenic shock or previous bypass surgery were excluded. Survival analysis for MACE (death, recurrent myocardial infarction (MI), stroke) was performed using the log-rank test before and after stratification by combined syntax score of the non-culprit vessels. Results: One hundred and nineteen patients with multivessel disease at index PCI for STEMI were included in the analysis (mean age 63.8 years (SD 12.8), male 81.5%, diabetes 13.4%, hypertension 35.3%, previous MI 18.5%, previous stroke 5.8%). Eighty-five (71%) patients underwent culprit only PCI and 34 (29%) underwent multivessel PCI. There were no differences in baseline variables between the two groups. Mean duration of follow up was 153.7 days (SD 137.4). MACE occurred in 14 patients from the culprit only PCI group (6 MI, 3 stroke and 6 deaths) while no events occurred in the multivessel PCI group (Figure 1 ). High syntax score (defined as >median) of the non-infarct vessels predicted increased MACE in the non-culprit PCI group (Figure 2 ). Conclusions: In this single centre, retrospective analysis, multivessel PCI was associated with significantly improved clinical outcomes when compared to culprit only PCI in patients presenting with STEMI and multivessel disease. Our findings provide support for the results of recently published clinical trials.